2010
DOI: 10.1017/s0007114510003429
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of BMI, calf circumference and mid-arm circumference in predicting subsequent mortality risk in elderly Taiwanese

Abstract: BMI, mid-arm circumference (MAC) and calf circumference (CC) are anthropometric indicators often included in geriatric health measurement scales. However, their relative effectiveness in predicting long-term mortality risk has not been extensively examined. The present study aimed to evaluate the relative effectiveness of these anthropometrics in predicting long-term mortality risk in older adults. The study prospectively analysed the ability of these indicators in predicting 4-year follow-up mortality risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 32 publications
3
64
0
2
Order By: Relevance
“…In Taiwan, the decrease in CP (26) increased the risk of death in men by 1.30 (RR: 1.22-1.71) and in women by 1.38 (RR: 1.15-1.48) . Although studies (23)(24)(25)(26) have shown that decreased CP increases the likelihood of decreased muscle mass, a study with elderly in Mexico (24) showed that CP increase (> 38 cm) had an independent association with disability, suggesting that the fat tissue may still impact muscle function.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Taiwan, the decrease in CP (26) increased the risk of death in men by 1.30 (RR: 1.22-1.71) and in women by 1.38 (RR: 1.15-1.48) . Although studies (23)(24)(25)(26) have shown that decreased CP increases the likelihood of decreased muscle mass, a study with elderly in Mexico (24) showed that CP increase (> 38 cm) had an independent association with disability, suggesting that the fat tissue may still impact muscle function.…”
Section: Discussionmentioning
confidence: 97%
“…The possibility of identifying elderly patients with reduced muscle mass through CP is reinforced by studies that have evaluated their ability to predict mortality (23)(24) and disability (24)(25) and need for care (26) . In Taiwan, the decrease in CP (26) increased the risk of death in men by 1.30 (RR: 1.22-1.71) and in women by 1.38 (RR: 1.15-1.48) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste contexto, indicadores antropométricos como Índice de Massa Corpó-rea (IMC) 8,9 , Peso 10 , Relação Cintura-Quadril (RCQ) 11,12 , Perímetro Braquial (PB) 13 , Perímetro da Panturrilha (PP) 14 e Circunferência da Cintura 15 são apontados como possíveis indicadores de alterações no estado nutricional e/ou capacidade física e/ou fragilidade.…”
Section: Introductionunclassified
“…Winter et al 27 observed that even in the community-dwelling older adults who have an annual health assessment, one in six is at risk of malnourishment, of whom one-third have a BMI of 25 kg/m 2 or higher. On the other hand, mid-arm circumference was found to be associated with risk of mortality in Taiwanese community-dwelling elderly (cut-off point of < 23.5 cm for men and < 22 cm for women) 28 . Ordoñez et al 29 observed that in hospitalized elderly, of the four assessment parameters of nutritional status (subjective global assessment, triceps skinfold thickness, BMI and mid-arm circumference), only mid-arm circumference showed an association with increased mortality.…”
Section: Discussionmentioning
confidence: 93%